2007
DOI: 10.4161/cc.6.9.4147
|View full text |Cite
|
Sign up to set email alerts
|

NFκB-Independent Signaling to the Cyclin D1 Gene by Rac

Abstract: AbbREviAtionsNFκB nuclear factor κB ERK extracellular signal-regulated kinase P-ERK dually phosphorylated ERK MEF mouse embryo fibroblast QPCR quantitative RT-PCR ACKnowlEdGEMEntsWe thank Jessie Villanueva and Hanqin Lei for generating some of the cyclin D1 promoterluciferase constructs described in this paper. This work was supported by NIH grants GM069064 and CA72639 to R.K.A. AbstRACtIn this report we characterize the mechanism of Rac-mediated cyclin D1 gene expression in mouse embryonic fibroblasts. Activa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
0
7

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 41 publications
3
20
0
7
Order By: Relevance
“…We do not yet know if the Rac-dependent signaling pathway(s) that leads to early-G1 phase cyclin D1 mRNA and mid-G1 phase cyclin D1 gene expression are the same or different. Evidence that they are different includes the observation that Rac-dependent induction of cyclin D1 in early-G1 phase requires concomitant signaling by NF-B, whereas its induction of cyclin D1 in mid-G1 phase is independent of NF-B (17).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We do not yet know if the Rac-dependent signaling pathway(s) that leads to early-G1 phase cyclin D1 mRNA and mid-G1 phase cyclin D1 gene expression are the same or different. Evidence that they are different includes the observation that Rac-dependent induction of cyclin D1 in early-G1 phase requires concomitant signaling by NF-B, whereas its induction of cyclin D1 in mid-G1 phase is independent of NF-B (17).…”
Section: Discussionmentioning
confidence: 99%
“…However, most studies on ERK and Rac signaling to cyclin D1 have either been performed in different cell types (epithelial versus mesenchymal) or under conditions of Rac overexpression (3,4,16,17). Thus, little is known about the potential interplay between endogenous ERK and Rac activities as it relates to expression of the cyclin D1 gene within a single cell type.…”
mentioning
confidence: 99%
“…Consistent with the redundant effects of integrins and E-cadherins on cyclin D1 expression in MCF10A cells, we find that both of these adhesion receptors use a Rac-dependent signaling pathway to induce cyclin D1 mRNA. We and others have previously shown that both ERK and Rac can induce cyclin D1 gene expression, but most of the studies with the Rac pathway have relied on overexpression of an activated Rac allele (Gjoerup et al, 1998;Joyce et al, 1999;Klein et al, 2007;Page et al, 1999;Westwick et al, 1997). We previously showed that endogenous Rac can induce cyclin D1 mRNA in fibroblasts, but this pathway is only seen upon deliberate inhibition of Rho (Welsh et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…RTKs and integrins also regulate the activation of Rac (RAC1), and integrin signaling additionally controls the coupling of Rac to its downstream targets (del Pozo et al, 2000). Although cyclin D1 is induced downstream of activated Rac (Joyce et al, 1999;Klein et al, 2007;Page et al, 1999), endogenous Rac signaling to cyclin D1 is not readily detected in fibroblasts because the pathway is inhibited by Rho (Welsh et al, 2001). …”
Section: Introductionmentioning
confidence: 99%
“…In several cell types, a sustained ERK activity between 3 and 6 h after mitogen stimulation results in the induction of cyclin D1 mRNA in mid-G 1 phase, at least when cells are re-entering G 1 phase from quiescence (22,23). A second common way to induce cyclin D1 mRNA is through Rac (24,25). Rac signaling to cyclin D1 requires NF-B and results in a somewhat earlier induction of cyclin D1 within the G 1 phase (23,26).…”
Section: And P21mentioning
confidence: 99%